Estimation of Probable Maximum Precipitation (PMP) in Manek Urai, Kelantan - Musa, Nadzirah (IRC, 2015)
Flood is a common disaster happened in Malaysia every year especially during November until December due to North East monsoon. This phenomenon had resulted in severe damages to lots of properties. The study is conducted in Manek Urai, Kelantan because this area is affected seriously during massive flood in 2014. Thus, hydrological study is conducted to estimate the Probable Maximum Precipitation (PMP). PMP is defined as the theoretical maximum precipitation for a given duration under modern meteorological conditions. Such a precipitation is likely to happen over a design watershed, or a storm area of a given size, at a certain time of year (WMO, 2009). The hydrological data obtained from DID will be developed for rainfall intensity for nine different durations which are 0.25, 1, 3, 6, 12, 24, 72, 120, and 168 hours. The slope of double mass curve must be not less than 0.9 to ensure the consistency of the raw data is acceptable. IDF Curves were developed for six different return period of 2, 5, 10, 20, 50, 100 years. Then PMP is calculated by using Hershfield Statistical Method and this PMP values is compared with other rainfall station nearby Manek Urai. The PMP value obtained in this study can be a reference for further study of flood. As a conclusion, this study is necessary flood in determining Probable Maximum Flood (PMF) and for safety structural design such as dam. Thus, it may reduce the total cost that government of Malaysia should bear to recover all losses during flood as the early warning are provided before the flood event happen.